The Political Costs of the 2009 British MPs’ Expenses Scandal
XIV, 221 p.
Keywords: This study examines the evolution and political consequences of the 2009 British MPs' expenses scandal. Despite claims of a revolution in British politics, we show how the expenses scandal had a limited, short-term impact.